A Comparison of Physical Activity Between Home-Based and Centre-Based Pulmonary Rehabilitation: A Randomised Controlled Secondary Analysis - Horton, Elizabeth J.; Ruksenaite, Justina; Mitchell, Katy; Sewell, Louise; Newby, Christopher; Singh, Sally J. (Frontiers in Rehabilitation Sciences, 2021)
Background: Pulmonary rehabilitation (PR) is a highly effective intervention for individuals with chronic obstructive pulmonary disease (COPD). Physical activity (PA) has been shown to increase after a centre-based programme, yet it is not clear if a home-based programme can offer the same benefit. This study aimed to evaluate the effect of home-based PR compared with the centre-based PR on the PA levels post 7 weeks of PR and 6 months follow-up. Method: In this study, 51 participants with COPD, of them, 36 (71%) men completed physical activity monitoring with a SenseWear Armband, at three time points (baseline, 7 weeks, and 6 months). The participants were randomly assigned to either centre-based supervised PR (n = 25; 69 ± 6 years; FEV1 55 ± 20% predicted) or home-based PR (n = 26; 68 ± 7 years; FEV1 42 ± 19% predicted) programmes lasting 7 weeks. The home-based programme includes one hospital visit, a self-management manual, and two telephone calls. The PA was measured as step count, time in moderate PA (3–6 metabolic equivalent of tasks [METs]) in bouts of more than 10 min and sedentary time (<2 METs). Results: Home-based PR increased step count significantly more than the centre-based PR after 7 weeks (mean difference 1,463 steps: 95% CI 280–2,645, p = 0.02). There was no difference in time spent in moderate PA was observed (mean difference 62 min: 95% CI −56 to 248, p = 0.24). Sedentary behaviour was also significantly different between the centre and home-based groups. The home group spent 52 min less time sedentary compared with the centre-based (CI −106 to 2, p = 0.039). However, after 6 months, the step count and time spent in moderate PA returned to baseline in both the groups. Conclusion: This study provides an important insight into the role of home-based PR which has the potential to be offered as an alternative to the centre-based PR. Understanding who may best respond from the centre or home-based PR warrants further exploration and how to maintain these initial benefits for the long-term. Trial Registry: ISRCTN: No.: ISRCTN81189044; URL: isrctn.com.